Sport Supplementation: Review Of Performance Enchasing Dietary Supplements Used In Sport - Peteva, Gergina; Ivanov, Valentin (European Scientific Journal, ESJ, 2016)
Performance enchasing substances have been used since ancient times in different sport disciplines and in all level of competition. Performance enchasing substances could be illicit drugs, prescription medicines (like Anabolic steroids) or dietary supplements as amino acids and vitamins. In this review we have summarised the benefits and the risks of supplementation in sport with different categories food additives. We have divided these products in following categories: food additives containing amino acids, food additives containing Tribulus Terrestris extract, containing Yohimbine, Dehydroepiandrosterone (DHEA), Vitamin E and Creatine.